ISOLATION AND HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY ANALYSIS OF CONDITIONAL AMINO ACIDS FROM THE FRESH LEAVES OF ALTERNANTHERA SESSILIS - S, SWARNAKUMARI; S, Mohan; VE, IDA CHRISTI; S, ABINAYA; S, KALAIVANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to isolate the conditional amino acids present in the fresh leaves extracts of Alternanthera sessilis and compare the isolated amino acids with amino acid standards. Method: The fresh plant material was used for extraction. For the extracted sample solution, paper chromatography and high-performance thin-layer chromatography (HPTLC) fingerprinting analysis were then carried out. Results: Since A. sessilis is rich in protein, various amino acids have been isolated in aggregates and paper chromatography has been performed. Amino acids were separated and identified using trial and error method. Cysteine, glycine, aspartic acid, and proline are the standard amino acids used for comparing with the isolated amino acids by HPTLC fingerprint analysis, which gives an idea for the authentication of the plant, its constituents and also provides a parameter for quality control. Conclusion: The results scientifically validate the use of A. sessilis in the traditional medicine and also as a food.